2008
DOI: 10.4103/0301-4738.39118
|View full text |Cite
|
Sign up to set email alerts
|

Learning micro incision surgery without the learning curve

Abstract: We describe a method of learning micro incision cataract surgery painlessly with the minimum of learning curves. A large-bore or standard anterior chamber maintainer (ACM) facilitates learning without change of machine or preferred surgical technique. Experience with the use of an ACM during phacoemulsification is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…We also agree with Thomas[5] who suggested that ACM allows anyone to learn SICS almost without a learning curve.…”
supporting
confidence: 89%
“…We also agree with Thomas[5] who suggested that ACM allows anyone to learn SICS almost without a learning curve.…”
supporting
confidence: 89%
“…Finally, if one wants to learn microincision cataract surgery, an ACM allows that almost without a learning curve. [7]…”
mentioning
confidence: 99%
“…Good patient selection is key to training MSICS surgeons. The ideal case should be immature cortical or LOC grade II-III nuclear sclerosis that can be molded through the scleral tunnel [4,5].…”
Section: Discussionmentioning
confidence: 99%